Practical Steps to Overcome Verbal Manipulation within Intercultural Foreign Language Education - Olesia Levina; Victoria Goncharova (ARPHA Proceedings, 2021)
The article reports on the study of verbal manipulation realized in mass-media discourse as a specific case of intercultural communication. It deals with the preparation of a new generation of intercultural communicants with new skills, ready to interact in the situation of manipulative influence realized by a partner of intercultural communication. The authors give some practical steps that can be implemented into a coursebook of teaching intercultural communication or media-communication in foreign-language university. The following idea is illustrated in the work: overcoming verbal manipulation within mass-media discourse can be achieved by transforming manipulative communicative strategy of foreign-language partner into conventional one by intercultural communicant. Formation of conventional (sub)competence identified by the authors in intercultural communicative competence can be realized within specific steps of communicative strategy of convention: 1) Identification of verbal manipulation; 2) Interpretation of verbal manipulation; 3) Comprehension of own position within manipulative influence; 4) Introspection of communicative behavior while intercultural communication in the situation of verbal manipulation.